Faâ€˜Äliyah Taâ€˜zÄ«z Dawr al-QÄnÅ«n li Taá¹wÄ«r Qiá¹Äâ€˜ al-á¸¤alÄl wa Taá¸¥wÄ«l MukhrajÄtihi ilÄ SÅ«q al-â€˜Amal - Ahmed, Ahmed Salem (Al-Ahkam, 2019)
á¸¤alÄl concept correlation with the industry and trade has shown a new matter leads to discovering other sciences to find the scientific basis for theÂ IslamicÂ principle that governs these matters, especially in the natural and economic sciences, but the different philosophy betweenÂ IslamicÂ science andÂ those sciences led to the dichotomy of research between the laboratories and jurisprudence groups. In spite of the high value of the output of both of them, but they are unable to translate it and linked it with the labor market, here where the researcher has felt the law role importance and its ability toÂ coordinateÂ these efforts and codify them as a reference in the á¸¥alÄl standard application and settlement of its disputes, which show the law-science creativityÂ  in á¸¥alÄl sector, by pointing the legalization importance and its direct connection with the rights and duties of those connected with the á¸¥alÄl sector.